2015
DOI: 10.1097/mib.0000000000000543
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Therapy for Inflammatory Bowel Disease

Abstract: Recent advances in inflammatory bowel disease (IBD) therapeutics include novel medical, surgical, and endoscopic treatments. Among these, stem cell therapy is still in its infancy, though multiple studies suggest the immunomodulatory effect of stem cell therapy may reduce inflammation and tissue injury in IBD patients. This review discusses the novel avenue of stem cell therapy and its potential role in the management of ulcerative colitis and Crohn’s disease. We conducted a comprehensive literature search to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 79 publications
1
64
1
2
Order By: Relevance
“…Furthermore, AMSCs expanded in human platelet lysate are zoonotic‐free cells that have promising potential for clinical orthopedic applications, based on their ability to differentiate into different types of mesenchymal cells, including those of the osteogenic, chondrogenic, and adipogenic lineages []. In addition to their capacity for multilineage differentiation, these cells may support tissue regeneration via their trophic and secretory functions, including anti‐inflammatory activity [, ]. During OA pathogenesis, joint inflammation promotes a catabolic state characterized by the loss of extracellular matrix, in which chondrocytes are susceptible to cell death and apoptosis [].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, AMSCs expanded in human platelet lysate are zoonotic‐free cells that have promising potential for clinical orthopedic applications, based on their ability to differentiate into different types of mesenchymal cells, including those of the osteogenic, chondrogenic, and adipogenic lineages []. In addition to their capacity for multilineage differentiation, these cells may support tissue regeneration via their trophic and secretory functions, including anti‐inflammatory activity [, ]. During OA pathogenesis, joint inflammation promotes a catabolic state characterized by the loss of extracellular matrix, in which chondrocytes are susceptible to cell death and apoptosis [].…”
Section: Introductionmentioning
confidence: 99%
“…These treatments have been evaluated in clinical trials on IBD patients with resistance to steroids and immunomodulating therapy. 75 MSCs are able to close the fistula tract due to their ability to differentiate and may be locally administered to treat those patients with complex perianal fistulae who are unresponsive to infliximab. 76 MSCs are effective in luminal disease because of their immunosuppressive potential.…”
Section: Current Therapeutic Strategiesmentioning
confidence: 99%
“…Multiple ongoing clinical trials have studied ASC in the treatment of patients with inflammatory bowel diseases (IBD) and other immune-mediated diseases 2,3 . ASCs are more frequently used for cell-based therapy given their ubiquity, ease of acquisition, and the high yield from adipose tissue.…”
mentioning
confidence: 99%
“…If MSC therapies are already clinically effective, why study them in mice? Unfortunately, the data from clinical trials using systemically administered MSCs for the treatment of mucosal lesions in IBD have shown good safety but no clear efficacy signal 2 . Although some studies have indicated that T regulatory (Treg) cell induction contributes towards the therapeutic benefits of MSC, the reasons for this are inadequately investigated, requiring additional mechanistic studies conducted in preclinical models to help understand the therapeutic benefits of MSC administration.…”
mentioning
confidence: 99%